FUNDAMENTALS OF OPTIMIZING INPATIENT CARE FOR CHILDREN - A.A. Baranov; S.A. Valillulina; N.N. Vaganov; E.V. Karpuchin ("Paediatrician" Publishers LLC, 2006)
Inpatient care for children has been considered to play an important role and to be influential in Russian healthcare system. However, a long lasting extensive development of health care system lacking sufficient finance and recourses has created a gap between the healthcare structure and capacity to provide healthcare and the needs of qualitative healthcare in the population. High number of limited ability hospitals without appropriate recourse base has already had its's day as a stage of inpatients care development. These hospitals could not provide a base for modern technology implementation and provision of present day high b quality medical care. Moreover, the current mechanism of financing «the hospital bed» but the patient has hampered medical care intensification and implementation of new technologies through loss of result orientation in medical specialists. Elaboration of efficacious means to optimize inpatient care would allow to control the rates assessing TH children's health in the country's population and to promote medical, social and economic efficacy of the inpatient care system. Key words: inpatient care, healthcare quality.